Appraising Qualitative Research for Evidence Syntheses: A Compendium of Quality Appraisal Tools. (November 2018) - Majid, Umair; Vanstone, Meredith
As the movement toward evidence-based health policy continues to emphasize the importance of including patient and public perspectives, syntheses of qualitative health research are becoming more common. In response to the focus on independent assessments of rigor in these knowledge products, over 100 appraisal tools for assessing the quality of qualitative research have been developed. The variety of appraisal tools exhibit diverse methods and purposes, reflecting the lack of consensus as to what constitutes appropriate quality criteria for qualitative research. It is a daunting task for those without deep familiarity of the field to choose the best appraisal tool for their purpose. This article provides a description of the structure, content, and objectives of existing appraisal tools for those wanting to evaluate primary qualitative research for a qualitative evidence synthesis. We then discuss common features of appraisal tools and examine their implications for evidence synthesis.